2021
DOI: 10.1080/19932820.2021.1909902
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of miRNAs in a human developing neuronal cell line chronically infected with Zika virus

Abstract: Zika virus (ZIKV) is a serious public health concern that may lead to neurological disorders in affected individuals. The virus can be transmitted from an infected mother to her fetus, via mosquitoes, or sexually. ZIKV infections are associated with increased risk for Guillain-Barré syndrome (GBS) and congenital microcephaly in newborns infected prenatally. Dysregulations of intracellular microRNAs (miRNAs) in infected neurons have been linked to different neurological diseases. To determine the potential role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“… 36 MiR-3687, miR-4725-3P, and miRNA-5096 are involved in pathways that regulate glial cell tumorigenesis in the nervous system. 37 - 39 The above studies can partly explain why the miRNA in this study has abnormal expression in schizophrenia, because the above processes may lead to the occurrence and development of schizophrenia. Previous studies have also shown that miRNAs associated with schizophrenia have something in common and are related to the exposure and response of stressor, 40 and the correlation between the activation level of stress response and schizophrenia has also been reported, which seems to explain the differential expression of some mRNAs in schizophrenia.…”
Section: Discussionmentioning
confidence: 74%
“… 36 MiR-3687, miR-4725-3P, and miRNA-5096 are involved in pathways that regulate glial cell tumorigenesis in the nervous system. 37 - 39 The above studies can partly explain why the miRNA in this study has abnormal expression in schizophrenia, because the above processes may lead to the occurrence and development of schizophrenia. Previous studies have also shown that miRNAs associated with schizophrenia have something in common and are related to the exposure and response of stressor, 40 and the correlation between the activation level of stress response and schizophrenia has also been reported, which seems to explain the differential expression of some mRNAs in schizophrenia.…”
Section: Discussionmentioning
confidence: 74%
“…We also identified several novel DE-miRNAs, including hsa-miR-548as-5p, hsa-miR-519c-3p, hsa-miR-6883-5p, hsa-miR-5186, hsa-miR-548ak, and hsa-miR-147a. The remaining DE-miRNAs have been implicated in infectious diseases 51 , endocrine diseases 52 and neoplastic diseases 53 56 , but not in CNS diseases or any cognitive disorders. Notably, changes in cellular developmental pathways do not yield the same outcome in every disease; in cancers, they cause rapid cell growth and proliferation, whereas in CNS disorders, they accelerate neuron aging and death.…”
Section: Discussionmentioning
confidence: 99%
“…The work performed by Sung et al, revealed anti-HIV-1 activity of miR-198 via targeting cyclin T1 [ 79 ]. Bagasra et al, found down-regulation of has-miR-5787 in Zika virus infected neuronal cell line [ 80 ]. A number of other studies have revealed down-regulation of miRNA targets of prioritized circRNAs in viral infections and other diseases.…”
Section: Discussionmentioning
confidence: 99%